Cumulative manufacturing capabilities in Europe: Integrating sustainability into the sand cone model. (10th November 2017) - Gold, Stefan; Schodl, Reinhold; Reiner, Gerald
Abstract: The purpose of this paper is to investigate the development of manufacturing capabilities in Central and Eastern Europe. In particular, top management's competitive priorities, plants' manufacturing strategies, and plants' manufacturing performances are compared between old and new European Union member states. Internationally collected data are compared using various analyses of covariance. The findings are interpreted against the background of the sand cone model, which is extended by integrating sustainability twice—that is, in its proactive and reactive forms. The results indicate that old and new member states dwell on different steps of cumulative manufacturing capability development. It is hypothesized that this can be attributed to differing labor costs; the requirements imposed by supply chains; and the pressure from stakeholders, such as civil society organizations. Our study responds to various calls to refine the sand cone model through the use of contingency theory by considering the operating conditions of plants in the two country groups as environmental contingency factors. Highlights: Manufacturing capabilities in old and new European Union members are compared. Different stages of cumulative manufacturing capability development are identified. Development stages are linked to operating conditions such as stakeholder pressures. Sand cone model is extended by integrating proactive and reactive sustainability. Short-term and long-term quest for competitiveness and sustainability is supported.